A study of the theory and practice of using the integrative and effective approach to the learning and teaching of Chinese characters to preschoolers = "You er zong he gao xiao shi zi fa" : li lun yu shi jian de yan jiu - Lee, Toi-na, Monique (The University of Hong Kong (Pokfulam, Hong Kong), 2015)
Currently, the pre-primary education curriculum in Hong Kong is using an Integrated Thematic Approach. In language learning, teaching activities are random and there is a lack of systematic teaching of Chinese characters. The aim of this study is to construct a theory in the teaching and learning of Chinese characters for preschoolers and to investigate the effectiveness of the “Young Children Integrative and Effective Approach” (IEA).